2013
DOI: 10.1021/ol402672e
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed C–P Cross-Coupling of Arylboronic Acids with P(O)H Compounds

Abstract: A novel and efficient Ni-catalyzed coupling of a wide range of arylboronic acids with H-phosphites, H-phosphinate esters, and H-phosphine oxides has been developed, providing a general and powerful tool for the synthesis of various aryl-phosphorus compounds, especially for valuable triarylphosphine oxides, in good to excellent yield. This protocol is the first Ni-catalyzed C-P bond-forming reaction between arylboronic acids and P(O)H compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(51 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…A plausible mechanism has been proposed in Scheme 1. While an elaborated study is required to fully understand the mechanism of the reported methodology, it is anticipated [39] that the active catalyst was generated when cobalt (II) salt was generated in the presence of the zinc powder and Alternatively, the addition of arylboronic acid to Co(0) in order to give Co(II) might be a possibility, which will be followed by transmetallation with the deprotonated phoshite, and finally, the reductive elimination leads to the formation of the cross-coupling product [31]. Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…A plausible mechanism has been proposed in Scheme 1. While an elaborated study is required to fully understand the mechanism of the reported methodology, it is anticipated [39] that the active catalyst was generated when cobalt (II) salt was generated in the presence of the zinc powder and Alternatively, the addition of arylboronic acid to Co(0) in order to give Co(II) might be a possibility, which will be followed by transmetallation with the deprotonated phoshite, and finally, the reductive elimination leads to the formation of the cross-coupling product [31]. Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…In 29, the signal of the same carbon atom could be found at 133. 6 The shifts indicated the presence of a C-S and not a C-O bond in the carbon skeleton [64,65], and the coupling constant value was typical for an γ-carbon atom present in a phosphine derivative [67][68][69].…”
Section: Methodsmentioning
confidence: 99%
“…The method is unsuitable for substrates with electron-donating groups or electron-withdrawing groups in the para-position of the aromatic ring. Recently, arylboronic acids were reported as new coupling partners with H-phosphonates, H-phosphinates, and H-phosphine oxides for nickel-catalyzed P-C bond formation [154].…”
Section: Cu- Ni- and Other Metal-catalyzed Reactionsmentioning
confidence: 99%